Pembangunan Pedesaan Berkelanjutan melalui Agrowisata Cerdas Berorientasi Maqasid Al-Syari’ah - Alda Fildza Amima; Lathifatul Mufidah; Taufikur Rohman; Danang Vanamai; Wahyu Wibowo (Yayasan Literasi Sains Indonesia, 2025)
This study aims to integrate the principles of Maqasid al-Shari’ah with the concept of smart agrotourism as a strategic approach to supporting sustainable rural development in the digital era. Through a literature review examining Maqasid theory, smart tourism, digital transformation, and rural development, the study identifies that Maqasid al-Shari’ah serves as an ethical foundation for guiding rural digitalization toward justice and public welfare. Integrating Maqasid al-Shari’ah values into smart agrotourism encourages the creation of efficient, environmentally conscious, and Sharia-compliant agricultural tourism that maintains a balance between economic benefits, cultural preservation, and the spiritual needs of rural communities. The study also highlights major challenges in rural digitalization, including infrastructure gaps, low digital literacy, and socio-cultural risks, indicating that development strategies must be context-based and participatory. This research recommends the development of an Islamic Smart Village Framework as a policy direction that integrates technology, community empowerment, and Islamic values in tourism village governance. For future research, empirical validation of the proposed conceptual model and the formulation of maqasid-based indicators for measuring rural well-being are needed. This study concludes by emphasizing the importance of advancing the paradigm of “Islamic Smart Village for a Sustainable Future” as the foundation for inclusive, ethical, and sustainable rural digital transformation.